Temporal and Isoform-Specific Expression of CTBP2 Is Evolutionarily Conserved Between the Developing Chick and Human Retina - Gage, Elizabeth; Agarwal, Devansh; Chenault, Calvin; Washington-Brown, Kameron; Szvetecz, Sarah; Jahan, Nusrat; Wang, Zixiao; Jones, Melissa K.; Zack, Donald J.; Enke, Ray A.; Wahlin, Karl J. (Frontiers in Molecular Neuroscience, 2022)
Complex transcriptional gene regulation allows for multifaceted isoform production during retinogenesis, and novel isoforms transcribed from a single locus can have unlimited potential to code for diverse proteins with different functions. In this study, we explored the CTBP2/RIBEYE gene locus and its unique repertoire of transcripts that are conserved among vertebrates. We studied the transcriptional coregulator (CTBP2) and ribbon synapse specific structural protein (RIBEYE) in the chicken retina by performing comprehensive histochemical and sequencing analyses to pinpoint cell and developmental stage-specific expression of CTBP2/RIBEYE in the developing chicken retina. We demonstrated that CTBP2 is widely expressed in retinal progenitors beginning in early retinogenesis but becomes limited to GABAergic amacrine cells in the mature retina. Inversely, RIBEYE is initially epigenetically silenced in progenitors and later expressed in photoreceptor and bipolar cells where they localize to ribbon synapses. Finally, we compared CTBP2/RIBEYE regulation in the developing human retina using a pluripotent stem cell derived retinal organoid culture system. These analyses demonstrate that similar regulation of the CTBP2/RIBEYE locus during chick and human retinal development regulated by different members of the K50 homeodomain transcription factor family.